Literasi Digital, Berpikir Kreatif Serta Kritis Dalam Pemecahan Masalah Oleh Murid SD di Jakarta Barat - Visensia Rini Anggraini; Laurens Kaluge (Departement of Mathematics Education, 2023)
The 21st century and revolution 4.0 have demanded students to be able to master high-level thinking skills (HOTS) and be able to take advantage of increasingly modern technology. This study aimed to discover the effects of digital literacy, creative thinking, and critical thinking on the problem-solving abilities of elementary school students in West Jakarta. Data collection was carried out using a survey system and closed questionnaires. From a sample of 117 students picked up from five clusters randomly of Dian Harapan Daan Mogot School representing primary schools in West Jakarta. Data analysis was a quantitative approach using regression. The results of the study show that digital literacy has a positive effect on the ability to solve problems. Digital literacy has a positive effect on checking information. Digital literacy skills do not have a positive effect on justification. Creative thinking has a positive effect on checking information. Creative thinking does not positively affect justification. Creative thinking has a positive effect on the ability to solve problems. Critical thinking positively affects the ability to solve problems.